ZDHHC11 modulates innate immune response to DNA virus by mediating MITA–IRF3 association. Issue 10 (October 2018) - Liu, Ying; Zhou, Qian; Zhong, Li; Lin, Heng; Hu, Ming-Ming; Zhou, Yan; Shu, Hong-Bing; Li, Shu
Abstract MITA is a central adaptor in innate immune responses to DNA viruses. The mechanisms responsible for recruitment of downstream kinase TBK1 and the transcription factor IRF3 to MITA remains enigmatic. Here we identified ZDHHC11, a member of DHHC palmitoyl transferase family, as a positive regulator of DNA virus-triggered signaling. Overexpression of ZDHHC11 activated the IFN-β promoter, while ZDHHC11-deficiency specifically impaired DNA virus HSV-1-induced transcription of downstream antiviral genes.Zdhhc11 −/− mice exhibited lower serum cytokine levels and higher lethality after HSV-1 infection. Mechanistically, ZDHHC11 facilitated the optimal recruitment of IRF3 to MITA. Our findings support an important role for ZDHHC11 in mediating MITA-dependent innate immune responses against DNA viruses.